The legend of Alexander of Macedon in the late mediaeval and early modern manuscripts of the Romanian principalities = Legenda Aleksandra Macedońskiego w późnośredniowiecznych i wczesnonowożytnych manuskryptach księstw rzymskich - Ionescu, Dan-Tudor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main aim of this quite long study was to draw an essential image of Alexander of Macedon as he appears through the pages of the Romanian "Alexandria": somehow the true essence of this hero and of his legend had eluded me many times. Compared with the Romanian "History of Troy", so faithful still to Homer and his epigonoi, the Romanian "Alexandria" seems to the untrained reader of old Romanian literature (like the author of these lines confesses to be) a collection of wild fantasy stories.
Keywords: Alexandria; Alexander of Macedon (356 p.n.e.-323 p.n.e.); Island of the Blessed; Island of Women; Amazons; Cleitarchus; Pseudo-Callisthenes; Nagomudrii; Gates of Paradise; Aleksandria; Aleksander Wielki (356-323); Wyspy Szczęśliwe; Wyspa Kobiet; Amazonki; Klejtarchos; Pseudo-Kallistenes; Bramy Raju